ANALISIS PERAN GERAKAN MAHASISWA KRISTEN INDONESIA (GMKI) CABANG JAMBI DALAM MEMBANGUN NILAI KARAKTER RELIGIUS KEKRISTENAN DI KOTA JAMBI - Lumban Gaol, Rijal Bahri; Hajri, Priazki; Tiara Maulia, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low implementation of GMKI Jambi's programs in fostering Christian religious character values in Jambi City. This study aims to identify the inhibiting factors in building Christian religious character values within GMKI Jambi. This research employs a descriptive qualitative approach. The informants involved in this study consist of regular members, board members of GMKI Jambi, and a pastor from the Huria Kristen Batak Protestant (HKBP) church. Data collection techniques include observation, interviews, and documentation. Furthermore, the data analysis techniques utilized involve data collection, data reduction, and data display. The results of the study indicate several key factors: low member participation in GMKI Jambi activities, internal dynamics among board members, an inability to balance time between academic responsibilities and organizational involvement, a lack of effort in engaging members, numerous unimplemented work programs, and low motivation among organizational leaders.